Pembangunan yang Responsif Gender melalui Musrenbang di Kabupaten Konawe - Sartiah Yusran (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2015)
This survey aims to determine the extent of understanding and knowledge of the women and the poor people about the importance of their involvement in the development and their understanding of their rights to participate in development through Musrenbang, as well as their expectations about the next steps. This survey focused on women and the poor in Konawe as the sample and population who have been determined from several representative that representing several districts of UNDP work areas (5 districts). The survey results indicate several things, namely: a) the term "musrenbang" (development planning) is popular among women and the poor. They often follow it; b) less than half of women and poor people who know the importance of musrenbang; c) the majority of women and poor people approve musrenbang but not all of them to assess the programs that have been planned and implemented able to address the problems of women and the poor; d) mostly women and poor people are not satisfied with their participation in development. Therefore, they consider it important to be involved optimally. Keywords: participation, responsive, gender, musrenbang